2008
DOI: 10.1074/jbc.m708630200
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitination by TOPORS Regulates the Prostate Tumor Suppressor NKX3.1

Abstract: The NKX3.1 gene located at 8p21.2 encodes a homeodomaincontaining transcription factor that acts as a haploinsufficient tumor suppressor in prostate cancer. Diminished protein expression of NKX3.1 has been observed in prostate cancer precursors and carcinomas. TOPORS is a ubiquitously expressed E3 ubiquitin ligase that can ubiquitinate tumor suppressor p53. Here we report interaction between NKX3.1 and TOPORS. NKX3.1 can be ubiquitinated by TOPORS in vitro and in vivo, and overexpression of TOPORS leads to NKX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
51
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 44 publications
(49 reference statements)
0
51
0
Order By: Relevance
“…Other studies have demonstrated that amino acid residues 184 to 196 harbor phosphorylation sites that regulate ubiquitin-mediated NKX3.1 degradation in response to the inflammatory cytokine TNF-␣ (24). In addition, the E3 ubiquitin ligase topoisomerase 1 binding, arginine/serine-rich, E3 ubiquitin ligase has been shown to polyubiquitinate and target NKX3.1 for proteasomal degradation (25). Interactions with TOPORS and other unidentified E3 ligases require specific regions within the NKX3.1 N and C termini (24,25).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have demonstrated that amino acid residues 184 to 196 harbor phosphorylation sites that regulate ubiquitin-mediated NKX3.1 degradation in response to the inflammatory cytokine TNF-␣ (24). In addition, the E3 ubiquitin ligase topoisomerase 1 binding, arginine/serine-rich, E3 ubiquitin ligase has been shown to polyubiquitinate and target NKX3.1 for proteasomal degradation (25). Interactions with TOPORS and other unidentified E3 ligases require specific regions within the NKX3.1 N and C termini (24,25).…”
mentioning
confidence: 99%
“…In addition, the E3 ubiquitin ligase topoisomerase 1 binding, arginine/serine-rich, E3 ubiquitin ligase has been shown to polyubiquitinate and target NKX3.1 for proteasomal degradation (25). Interactions with TOPORS and other unidentified E3 ligases require specific regions within the NKX3.1 N and C termini (24,25).…”
mentioning
confidence: 99%
“…Androgen-responsive LNCaP cells (passage number [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] were propagated in RPMI1640 (Invitrogen, UK) medium supplemented with 10% heat-inactivated FBS (Invitrogen, UK). Cells were serum starved in the presence of 2% for 48 h and 0.5% for an additional 24 h in CT-FBS containing RPMI1640.…”
Section: Propagation and Androgen Inductionmentioning
confidence: 99%
“…However, as part of the Groucho complex, NKX3.1 is required to repress transcription with its loss resulting in prostatic epithelial dysplasia and benign hyperplasia of the rat prostate [10,11]. Ouyang et al, have shown that NKX3.1 suppresses tumor initiation by protecting the cell against oxidative damage via transcriptional regulation of the pro-oxidant enzyme levels [12,13]. TOPORS, a strong E3 ubiquitin ligase, promotes proteasomal degradation of NKX3.1 through direct interaction, predisposing cells to oncogenic transformation by providing an irreversible growth advantage as the first steps in prostate carcinogenesis [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation